Synthesis, Antioxidant, and Xanthine Oxidase Inhibitory Activities of 5‐[4‐[2‐(5‐Ethyl‐2‐pyridinyl)ethoxy]phenyl]methyl]‐2, 4‐thiazolidinedione Derivatives. Issue 4 (16th December 2013) - Begum, A. Bushra; Begum, Muneera; Ranganatha, V. Lakshmi; Prashanth, T.; Zameer, Farhan; Hegdekatte, Raghavendra; Khanum, Shaukath Ara
<x xml:space="preserve">Abstract</x> Xanthine oxidase (XO) is a complex metalloflavoprotein, the overproduction of which usually leads to a pathological condition called gout. The XO inhibitors may prove to be promising antigout agents. The XO generates superoxide anions and H2O2 for the self‐defense system of the organism. Abnormal production of this superoxide (reactive oxygen species) is responsible for a number of complications including inflammation, metabolic disorder, cellular aging, reperfusion damage, atherosclerosis, and carcinogenesis. In this paper, we report the synthesis of N‐substituted analogs of thiazolidinedione derivatives as effective and new class of XO inhibitors and also as antioxidant agents. Among all the compounds in the series, compound 2i produced relatively better activity against human milk XO (72% inhibition), which was also supported by docking studies.